Peran Kepala Desa dalam Pemberdayaan Kelompok Budidaya Ikan “Mina Karya” di Desa Babakan, Kecamatan Pangandaran, Kabupaten Pangandaran - Rusti Oktavian; Regi Refian Garis; Asep Nurdin Rosihan Anwar (PT. PENERBIT TIGA MUTIARA, 2024)
Strengthening Village communities improves living standards, produces sustainable benefits for the community, encourages community independence and initiative, develops the Village economy, improves the environment, and forms community financial institutions, are efforts to create activities that make this possible. Increasing the creativity and productivity of the people of Babakan Village who face several obstacles in strengthening the fish cultivation population, including the dry season causing drought, this has an impact on the development of fish cultivation, the outreach and training by the Babakan Village Government for fish cultivation groups regarding their potential, the cultivator community has not been maximized. Fish lack insight and knowledge so that fish farming management is carried out by autodidacts. The conclusions obtained show that the role of the village government in strengthening the